Texture Exposure of Unconventional (101)Zn Facet: Enabling Dendrite‐Free Zn Deposition on Metallic Zinc Anodes - Cheng, Zihai; Wang, Ke; Fu, Jimin; Mo, Funian; Lu, Peng; Gao, Jiantou; Ho, Derek; Li, Bo; Hu, Haibo (Advanced energy materials, 2024)
Texturing metallic zinc anodes (MZAs) for selective exposure of (002)Zn plane with high thermodynamical stability is an efficient scheme for dendrite‐free Zn electrodeposition. However, fundamental factors that influence Zn deposition morphology via surface crystallographic texture engineering are not well understood. Herein, different from traditional cognition, MZAs with preferential exposure of (101)Zn facet are demonstrated to be equally effective in promoting dendrite‐free Zn deposition, which is enabled by introducing trace amount (0.01 m) of theophylline into ZnSO4 electrolyte. Experimental results and mathematical model corroborate, indicating mechanistically that the theophylline derived cations preferentially adsorb on the (002)Zn crystal plane due to higher adsorption energy, thereby accelerating its growth through increased binding affinity with Zn2+ ions. Consequently, this phenomenon facilitates the texture exposure of (101)Zn facet to achieve ordered surface crystallographic orientation of MZAs (101‐Zn), thus enabling electrodeposition/dissolution cycling over 650 h under a depth of discharge up to 40% and significantly boosting the rechargeability (76.7% capacity retention after 1000 cycles) of the 101‐Zn||carbon‐cloth@MnO2 full battery relative to counterpart without theophylline additive (36.3%). The work offers deep insights on the scientific links between the surface crystallographic orientation of MZAs and Zn deposition morphology, while opens up vast untapped opportunities to realize dendrite‐free MZAs. Dendrite‐free Zn deposition on metallic zinc anodes (MZAs) enabled by texture exposure of unconventional (101)Zn facet is demonstrated by introducing trace amount of theophylline into ZnSO4 electrolyte, which removes the prior believed constraint of realizing uniform Zn growth by preferential exposing conventional (002)Zn plane, thus significantly expanding the design space available for crystallographic texturing of Zn surface to overcome dendrites proliferation.